2014
DOI: 10.1007/s11999-014-3642-6
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Long-term In Vivo Bearing Mobility in Eight Rotating-platform TKAs

Abstract: Background Posterior-stabilized rotating-platform prostheses for TKAs were designed to improve contact mechanics at the femoral-polyethylene (PE) interface. Short-term followup studies have shown that the PE bearings rotate with respect to the tibia but might not necessarily track with the femur. It is important to know how kinematics in these designs change owing to longterm in vivo use.Questions/purposes We asked whether there is a significant change in the in vivo kinematic performance of a posterior-stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…Both analysed systems have central pivoting rotating platform designs, which could result in an ipsilateral rollback of one condyle and roll‐forward of the contralateral condyle during deep flexion [13, 29]. Since no significant difference was observed in femoro‐tibial rotation, the observed significant difference in femoro‐tibial translation is most likely caused by an actual rollback, specifically in the G‐CURVE design.…”
Section: Discussionmentioning
confidence: 99%
“…Both analysed systems have central pivoting rotating platform designs, which could result in an ipsilateral rollback of one condyle and roll‐forward of the contralateral condyle during deep flexion [13, 29]. Since no significant difference was observed in femoro‐tibial rotation, the observed significant difference in femoro‐tibial translation is most likely caused by an actual rollback, specifically in the G‐CURVE design.…”
Section: Discussionmentioning
confidence: 99%
“…This is noteworthy, as determining the appropriate time to evaluate TKA performance is somewhat controversial and highly dependent on the outcomes to be assessed. At the time of publication, only three longitudinal studies reported fluoroscopic knee kinematics [21, 37, 41]. However, all of these studies examined kinematics for PS‐RP TKAs.…”
Section: Discussionmentioning
confidence: 99%
“…In another study examining fluoroscopic kinematics of a PS‐RP design [21], patients were recorded performing a deep knee bend at 3 months, 15 months, 5 years, and 10 years after TKA. Only the axial rotation between the femoral component and the polyethylene insert was significantly reduced at the 10‐year timepoint compared to all earlier evaluations [21]. There were no statistical differences in tibial internal rotation, medial condyle AP translation, and lateral condyle AP translation between any of the postoperative intervals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations